Genome mining, isolation, chemical synthesis and biological evaluation of a novel lanthipeptide, tikitericin, from the extremophilic microorganism Thermogemmatispora strain T81. Issue 37 (12th September 2018) - Xu, Buzhe; Aitken, Emma J.; Baker, Benjamin P.; Turner, Claire A.; Harvey, Joanne E.; Stott, Matthew B.; Power, Jean F.; Harris, Paul W. R.; Keyzers, Robert A.; Brimble, Margaret A.
Abstract : Tikitericin, a novel lanthipeptide was isolated and characterised together with its first total synthesis. Abstract : Genome mining of the New Zealand extremophilic microorganism Thermogemmatispora strain T81 indicated the presence of biosynthetic machinery to produce several different peptidic natural products. Solid-phase culture of T81 led to the isolation of tikitericin1, a new lanthipeptide characterised by four (methyl)lanthionine bridges. The mass-guided isolation and structural elucidation of tikitericin1 is described together with its total synthesis via Fmoc-solid-phase peptide synthesis (SPPS). The key non-canonical (methyl)lanthionine residues were synthesised in solution phase via an improved synthetic route and subsequently assembled to construct the peptide backbone using Fmoc-SPPS. N-Terminal truncated analogues of tikitericin (2–5 ) were also prepared in order to evaluate the contribution of each sequential ring of the polycyclic lanthipeptide to the antibacterial activity.